Das Gedächtnis des Schreibers B4/E. Ein Experiment zum Eingangsteil des Nibelungenliedes - Stephan Muller (Filologia Germanica, 2024)
THE MEMORY OF SCRIBE B4/E. AN EXPERIMENT WITH THE OPENING SECTION OF THE ‘NIBELUNGENLIED’. The paper discusses the consequences emerging from the identity of scribe B4/E, who wrote in the following codices: St. Gall, Stiftsbibliothek, Cod. 857 (Nibelungenlied, manuscript B); Berlin, Staatsbibliothek Preußischer Kulturbesitz, Fragm. 44 (Nibelungenlied, fragment E); Vienna, Österreichische Nationalbibliothek, Cod. 13070 (Parzival, fragment a). It is argued that this identity leads to the existence of ‘Reminiszenzlesarten’ in the initial part of the Nibelungenlied in manuscript B (St. Gall, Cod. 857).